Etiological Role of Cytomegalovirus in Type 1 Diabetes Mellitus - Madoori, Srinivas; C, Ramya; B, Sridevi; Gundapuneni, Ravali (Indian Journal of Case Reports, 2015)
Cytomegalovirus is a double stranded DNA virus belonging to herpes virus family. The infection once acquired persistslifelong. The transmission of cytomegalovirus infection from mother to child may occur either in utero or perinatally. The risk of transmission to the fetus as a function of gestation age is uncertain, but infection during early gestation carries a higher risk of severe fetal disease. The incidence of Type 1 diabetes mellitus is rising continuously all over the world and this may be due to multiple factors. The role of cytomegalovirus in the etiology of diabetes mellitus is controversial. Here, we report a case of 35 months female child having Type 1 diabetes mellitus with congenital cytomegalovirus disease.